Prevalence of atrial fibrillation and antithrombotic therapy in a group of primary health care clinics in the North of Portugal - Oliveira, Diana (2014)
Objectives: To determine the prevalence of atrial fibrillation among patients in primary health care clinics in West Porto in May 2013, to assess the distribution of CHA2DS2VASc risk factors for thromboembolism, to study antithrombotic therapy and the sites where anticoagulation therapy is managed. Type of Study: Cross-sectional study. Setting: Primary Health Care Centres of West Porto. Population: Patients registered in the health units of West Porto. Methods: Data were collected from the electronic medical records using SIARS, MIM@UF and SAM software. The chi-squared statistic was used for comparison of proportions, with statistical significance set at the p < 0.05 level. Results: The authors identified 1628 people with atrial fibrillation. Of these 58% were female. They ranged in age from 29 to 104 years with a mean age of 76 ± 11 years. The prevalence of atrial fibrillation was 0.98%, with a prevalence of 1.77% in patients over 39 years. The CHA2DS2VASc score was greater than zero in 95% of patients, excluding cases where female gender was the only risk factor. The main risk factors were arterial hypertension (75%), age greater than 74 years (62%) and female gender. Anticoagulation therapy was prescribed to 68% of patients with 88% receiving vitamin K antagonists. Follow-up of anticoagulation was performed in clinical laboratories in 74% of cases. Conclusions: The prevalence of atrial fibrillation in this population was greater than that reported in a national study in 2006 (0.5%). However the prevalence in patients over 39 years of age was less than that found in a study conducted in 2010, using electrocardiographic diagnosis (2.5%). Identification of patients with atrial fibrillation is an important task in primary health care.